Χάρης Πλουμίδης, Ορεστειάδα, Υπό την αιγίδα της Πανελλήνιας Ομοσπονδίας Εκδοτών Βιβλιοπωλών, Κωνσταντινούπολη Komal, 21999, σ.σ. 108 - Κατσιγιάννη Άννα (Σύγκριση/Comparaison/Comparison, 2017)
[Δε διατίθεται περίληψη]